Pijat Tui Na sebagai Upaya Meningkatkan Nafsu Makan pada Balita di Pustu Munding - Nova Harianti; Ruliana Isna Rosida; Yulia Nur Khayati; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2024)
Child growth and development is a very important issue and needs serious attention. Growth can be seen from body weight and head circumference, while development can be seen from motor skills, social, emotional, language skills and cognitive abilities. Children's growth and development is influenced by several factors, one of which is influenced by nutritional status. Efforts to overcome feeding difficulties in toddlers can be done using non-pharmacological methods through tui na massage. Tui na massage is one way to overcome feeding difficultiestoddlers, carried out for 6 consecutive days before eating for 30 minutes with 8 series of massages that can overcome eating difficulties. The aim of this community service is to apply tui na massage as a complementary therapy to overcome feeding difficulties in toddlers. Method: Implementation of activities in the form of tui na massage training for mothers of toddlers using lecture, discussion and practice methods. The conclusion obtained after this community service were the pre – test result of respondents in the good knowledge category (50%) in the poor category (30%) and the post - test result 0f 100 % of respondents in the good knowledge category. Apart from that, the skills of the posyandu respondents are also in the good category, shown by the evaluation result with a score of (98%). Abstrak Pertumbuhan dan perkembangan anak merupakan masalah yang sangat penting dan perlu mendapatkan perhatian yang serius. Pertumbuhan dapat dilihat dari berat badan dan lingkar kepala, sedangkan perkembangan dapat dilihat dari kemampuan motorik, sosial, emosional, kemampuan berbahasa, serta kemampuan kognitif. Pertumbuhan dan perkembangan anak dipengaruhi oleh beberapa faktor salah satunya dipengaruhi oleh status gizi. Upaya untuk mengatasi kesulitan makan pada balita dapat dilakukan dengan cara non farmakologi melalui pijat tui na. Pijat tui na merupakan salah satu cara untuk mengatasi kesulitan makan pada balita, dilakukan selama 6 hari secara berturut turut sebelum makan selama 30 menit dengan 8 rangkaian pijat yang dapat mengatasi kesulitan makan. Tujuan dari pengabdian masyarakat ini untuk menerapkan pijat tui na sebagai terapi komplementer untuk mangatasi kesulitan makan pada balita.Metode: Pelaksanaan kegiatan berupa pelatihan pijat tui na pada ibu balita dengan metode ceramah, diskusi dan praktik. Kesimpulan yang didapatkan setelah pengabdian masyrakat ini adalah hasil pre – test responden dalam kategori pengetahuan baik (50%) kategori pengetahuan baik. Selain itu, keterampilan para responden posyandu juga dalam kategori baik ditunjukkan dengan hasil evaluasi nilai (98%).